1977
DOI: 10.1113/jphysiol.1977.sp012065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of related sensory inputs on motor performances in man studied through changes in perceived heaviness

Abstract: SUMMARY1. The perception of the heaviness of lifted objects was studied using a weight-matching task when sensory inputs from parts related to the lifting task were altered.2. A weight lifted by flexing the index finger feels heavier when the thumb is anaesthetized and lighter when the thumb is electrically stimulated. A weight lifted by flexing the distal joint of the thumb feels heavier when the sensory input from the skin and joint of the thumb is abolished by anaesthesia. It also feels heavier when the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
3

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 28 publications
4
53
0
3
Order By: Relevance
“…However, the relative matching force of the fatigued triceps estimated extremely closely the relative reference force of the contralateral non-fatigued homologous muscle (Carson et al 2002). Despite of differences in the maximal force generating capacity between non-homologous muscles or altered maximal force generating capacity in one of the homologous muscles, the observation of relative force matching suggests that force perception is likely to be based on a "sense of effort" in contralateral matching paradigms (Gandevia and McCloskey 1977b;Gandevia and McCloskey 1977a;Gandevia 1987;Carson et al 2002).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the relative matching force of the fatigued triceps estimated extremely closely the relative reference force of the contralateral non-fatigued homologous muscle (Carson et al 2002). Despite of differences in the maximal force generating capacity between non-homologous muscles or altered maximal force generating capacity in one of the homologous muscles, the observation of relative force matching suggests that force perception is likely to be based on a "sense of effort" in contralateral matching paradigms (Gandevia and McCloskey 1977b;Gandevia and McCloskey 1977a;Gandevia 1987;Carson et al 2002).…”
Section: Introductionmentioning
confidence: 83%
“…A contralateral force matching paradigm has been commonly used to investigate mechanisms of force perception and control (Gandevia and McCloskey 1977b;Gandevia and McCloskey 1977a;Cafarelli and Bigland-Ritchie 1979;Kilbreath et al 1997;Carson et al 2002;Jones 2003;Jones and Piateski 2006). In this paradigm, a reference force produced by one muscle group is matched by a matching force produced by the same (homologous) or different (nonhomologous) muscle groups of the contralateral limb.…”
Section: Introductionmentioning
confidence: 99%
“…Force is perceived according to a combination of peripheral inputs and descending motor commands. Descending motor commands are modified by concurrent peripheral inputs (Gandevia and McCloskey 1977b;Kilbreath et al 1997), resulting in an altered relationship between the sense of effort and descending commands after fatigue (cf. Carson et al 2002).…”
Section: Mismatch Of Finger Force Estimation After Fatiguementioning
confidence: 99%
“…Muscle spindle afferents are also more active when the efferent input to a muscle increases (Vallbo, 1971), but they do not appear to be responsible for the change in perceived force, since, during muscle tendon vibration, their discharge rate increases and yet the perceived force of contraction is diminished (McCloskey et aI., 1974). Joint and cutaneous receptors have been shown to contribute to the perception of force (Gandevia & McCloskey, 1977), but following joint and skin anesthesia, Roland and Ladegaard-Pedersen (1977) found that judgments of force did not differ from those obtained under normal conditions. Although the present experiment did not address the issue of the relative importance of peripheral sensory receptors in perceived force, it is of interest to establish the physiological basis of force perception.…”
Section: Endurance Time (Sec)mentioning
confidence: 99%